Reconfigurable scattering by liquid crystal–polymer composite - Duan-Yi Guo; Yan-Ting Liu; Chen-Wei Tu; Iam Choon Khoo; Tsung-Hsien Lin (APL Materials)
Scattering phenomena offer significant application potential in fields such as high-resolution imaging, sensing, material characterization, and photonic computing due to their random-walk behavior and intricate spatial intensity statistics. A key to enhanced performance is to generate or reconfigure scattered light with tailored statistics to meet the specific requirements of various applications. Existing methods for reconfiguring scattering often rely on spatial light modulators and computational tools, which invariably involve complex algorithms and are constrained by limited spatial resolution and lack of control over polarization responses. In this work, we investigate the modulation of scattering statistics with a liquid crystal–polymer composite (LCPC) under varying applied voltages. By leveraging the electro-optic properties of LCPCs, the morphology and types of the reconfigured speckles can be dynamically adjusted between Rayleigh and non-Rayleigh with good stability. In addition, the polarization characteristics of the reconfigured speckles can be modulated, introducing another degree of freedom in scattering reconfiguration. These findings underscore the potential of LCPCs as a promising platform for reconfiguring scattering, offering new possibilities in adaptive optics, neuromorphic computing, and imaging-related applications.